Jasmonates: News on Occurrence, Biosynthesis, Metabolism and Action of an Ancient Group of Signaling Compounds - Wasternack, Claus; Strnad, Miroslav (International journal of molecular sciences, 2018)
: Jasmonic acid (JA) and its related derivatives are ubiquitously occurring compounds of land plants acting in numerous stress responses and development. Recent studies on evolution of JA and other oxylipins indicated conserved biosynthesis. JA formation is initiated by oxygenation of α-linolenic acid (α-LeA, 18:3) or 16:3 fatty acid of chloroplast membranes leading to 12-oxo-phytodienoic acid (OPDA) as intermediate compound, but in Marchantiapolymorpha and Physcomitrellapatens, OPDA and some of its derivatives are final products active in a conserved signaling pathway. JA formation and its metabolic conversion take place in chloroplasts, peroxisomes and cytosol, respectively. Metabolites of JA are formed in 12 different pathways leading to active, inactive and partially active compounds. The isoleucine conjugate of JA (JA-Ile) is the ligand of the receptor component COI1 in vascular plants, whereas in the bryophyte M. polymorpha COI1 perceives an OPDA derivative indicating its functionally conserved activity. JA-induced gene expressions in the numerous biotic and abiotic stress responses and development are initiated in a well-studied complex regulation by homeostasis of transcription factors functioning as repressors and activators.
Keywords: cyklopentany; Metabolic Networks and Pathways; mastné kyseliny; JA signaling; Cyclopentanes; active JA compounds; oxylipiny; Fatty Acids; peroxizomy; mechy; druhová specificita; metabolické sítě a dráhy; Species Specificity; Chloroplasts; transcription factors; Marchantia; alpha-Linolenic Acid; Fatty Acids, Unsaturated; Oxylipins; Jasmonic acid (JA) metabolites; chloroplasty; kyselina alfa-linolenová; occurrence; nenasycené mastné kyseliny; JA biosynthetic enzymes; Bryopsida; Peroxisomes; JA bypass